Role of Enzymes in Synthesis of Biologically Important Organic Scaffolds: A Review - Gupta, Khushbu; Chundawat, Tejpal Singh (Asian Journal of Chemistry, 2019)
Green route of biogenic synthesis of heterocyclic compounds via microbes (bacteria, fungi, virus, yeast, algae, etc.) has the potential to deliver clean manufacturing technology. The application of biocatalysts for the synthesis of novel compounds has attracted increasing attention over the past few years and consequently, high demands have been placed on the identification of new biocatalysts for organic synthesis. Enzymes play an increasingly important role as biocatalysts in the synthesis of key intermediates for the pharmaceutical and chemical industry, and new enzymatic technologies. The characteristics of biocatalyst can be tailored with protein engineering and metabolic engineering methods to meet the desired process conditions. This review discusses the synthetic application of all the six classes of enzymes which are oxidoreductase, transferase, hydrolase, lyase, isomerase and ligase. Enzymes are highly selective catalysts and their contribution to regio-, chemo- and stereoselectivity of compounds were also discussed.